Simulation Of Optimal Portfolio Using Single Index Model and Markowitz Model On Lq-45 Index Shares For 2018 - Puji Lestari, Novi (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2021)
The essence of portfolio formation is to reduce risk by means of diversification, namely allocating a number of funds to various investment alternatives that are negatively correlated. To select returns in a portfolio, you can use the Single Index Model and the Markowitz Model. This study was conducted with the aim of comparing the calculation of which company portfolios can provide a good rate of return with a small risk using the Single Index and Markowitz Model based on the sector of the company. So that the results of this study can provide recommendations to investors in decision making on portfolio selection. The research was conducted on companies indexed by LQ 45 on the Indonesia Stock Exchange. The research period is to use companies indexed by LQ 45 in 2018 for two periods.